Keanekaragaman Spesies Famili Myrtaceae Tepian Sungai Barito, Desa Sungai Gampa Kabupaten Barito Kuala Kalimantan Selatan - Sasmita, Sasmita; Dharmono, Dharmono; Suyidno, Suyidno (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
The riparian zone of the Barito River is an important ecosystem, yet its utilization patterns by indigenous communities in the area remain relatively limited. The lack of comprehensive data may hinder efforts in documentation, conservation, and the management of biological resources based on local wisdom. This study aims to document the diversity of plant species used by the Dayak Bakumpai community along the banks of the Barito River in Sungai Gampa Village, Barito Kuala Regency, South Kalimantan. The research will be conducted from August to September 2025 using a descriptive exploratory design with both qualitative and simple quantitative approaches. Data will be collected through field observations using an exploration method to record morphological characteristics of roots, stems, leaves, flowers, and fruits. The results identified nine plant species, namely Syzygium aqueanum (water apple), Syzygium polyanthum, Syzygium malaccense (L.) Merr., Psidium guajava (red guava and white guava), Melaleuca cajuputi Powell (large-leaf and small-leaf galam), and Melastoma candidum, with the genus Syzygium dominating in terms of species number. The utilization of these plants by the community includes fruit as a food source, traditional medicine, and essential oil production, demonstrating the close relationship between riparian plant diversity and the socio-economic needs of the local community. This inventory provides baseline data on the riparian flora of the Barito River, which is valuable for biodiversity documentation, vegetation monitoring, and community-based riparian area management.